Little Pim, fun with languages: English/ESL.1,Eating and drinking (Little Pim, ,, 2009)
Alternates animated sequences of a panda bear named Little Pim with live action sequences of children enjoying everyday activities to teach babies, toddlers, and preschoolers over 60 mealtime-related English/ESL vocabulary words. Includes vocabulary reviews and a repeat play option.
Disc 1. Eating and drinking , disc 2. Wake up smiling , disc 3. Playtime.

Little Pim, fun with languages: Mandarin Chinese6,I can count (Little Pim, ,, 2010)
A Mandarin DVD introducing another 180 words and phrases in different themes. The teacher interacts with real children in beautifully filmed high-definition video. Once kids learn to count to ten they want to do it again and again. Join Little Pim and friends as they count all sorts of fun objects from ladybugs to lollipops to dancing feet.

Little Pim, fun with languages: English/ESL.3,Playtime (Little Pim, ,, 2008)
Little Pim takes place entirely in the foreign language while showing children enjoying everyday activities. In Playtime, join Little Pim and pals in the wonders of play, from blocks to boats to tea parties. See the original and funny ways young children play together, while learning new words for your little one's explorations.

Little Pim, fun with languages: Arabic.1,Eating and drinking (Little Pim, ,, 2009)
See Little Pim and friends making and eating food while having a great time discovering new tastes. The Eating and Drinking Arabic DVD contains more than 60 words and phrases.

Little Pim, fun with languages: English/ESL.5,Happy, sad and silly (Little Pim, ,, 2011)
Experience a wide range of emotions with Little Pim from happiness to love, to sad faces, mad faces, and everything in between. Introduces 60 new English words and phrases.

Little Pim, fun with languages: French.2,Wake up smiling (Little Pim foreign language and fun, ,, 2007)
Teaches French vocabulary to babies, toddlers and preschoolers. Features an animated panda bear named Little Pim, and is presented in the French language while showing children enjoying everyday activities. Follow Little Pim and pals as they wake up to a new day and go to sleep after a busy day, while teaching more than 60 words for morning and evening routines.
Special feature: Interview with founder.

Little Pim, fun with languages: Mandarin Chinese3,Playtime (Little Pim foreign language and fun, ,, 2007)
Features an animated panda bear named Little Pim. The video is entirely in Mandarin, showing children enjoying everyday activities. The series can be viewed in any order.

Little Pim, fun with languages: Mandarin Chinese1,Eating and drinking (Little Pim foreign language and fun, ,, 2007)
Features an animated panda bear named Little Pim. The video is entirely in Mandarin, showing children enjoying everyday activities. The series can be viewed in any order.

Little Pim: Let's learn Chinese,Disc 4,At home (Little Pim Corporation, 2013)
60 words and phrases from windows to gardens to stairs to mailboxes as Little Pim and friends explore their home and yard. -- Container.

Little Pim, fun with languages: French.4,In my home (Little Pim Corp, 2010)
A French DVD introducing another 180 words and phrases in different themes. The animated teacher interacts with real children in beautifully filmed high-definition video. Come along with Little Pim and friends as they play with their toys and explore the different rooms in a home, in both apartments and houses.